2016
DOI: 10.1038/srep34494
|View full text |Cite|
|
Sign up to set email alerts
|

A proteinaceous organic matrix regulates carbonate mineral production in the marine teleost intestine

Abstract: Marine teleost fish produce CaCO3 in their intestine as part of their osmoregulatory strategy. This precipitation is critical for rehydration and survival of the largest vertebrate group on earth, yet the molecular mechanisms that regulate this reaction are unknown. Here, we isolate and characterize an organic matrix associated with the intestinal precipitates produced by Gulf toadfish (Opsanus beta). Toadfish precipitates were purified using two different methods, and the associated organic matrix was extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Reggi et al (26) and Falini et al (27) showed that the organic matrix proteins extracted from coral skeletons stabilize ACC in vitro in the absence of cells. ACC stabilization by proteins was also observed in sea urchin spicules (32) and in fish intestines (49). These proteins, therefore, may be in the same vesicles as ACC.…”
Section: Model For Caco 3 Biomineralization Via Amorphous Precursor Pmentioning
confidence: 68%
“…Reggi et al (26) and Falini et al (27) showed that the organic matrix proteins extracted from coral skeletons stabilize ACC in vitro in the absence of cells. ACC stabilization by proteins was also observed in sea urchin spicules (32) and in fish intestines (49). These proteins, therefore, may be in the same vesicles as ACC.…”
Section: Model For Caco 3 Biomineralization Via Amorphous Precursor Pmentioning
confidence: 68%
“…However, temperature effects on magnesium uptake are not always clear and can be overridden or distorted by biological controls (so-called "vital effects", sensu Urey et al 1951), solution pH (Lea et al 1999), and the ratio of Mg to Ca in solution (Mewes et al 2014). Within the piscine intestine, proteins capable of regulating magnesium uptake, precipitation rate, and precipitate morphology, at least in vitro, offer a potential organic control (Schauer et al 2016(Schauer et al , 2018Schauer and Grosell 2017), while somewhat variable and often high values of pH, [Mg] 2+ , and Mg/Ca are likely important inorganic controls (Wilson et al 1996;Grosell et al 2001). Intriguingly though, the sole available data point for temperate fish carbonates is consistent with a temperature effect: 10 mol% MgCO 3 in HMC produced at 13 C (Wilson et al 2009) being low compared with typical values of 20-40 mol% from warm-water settings (20-27 C-Walsh et al 1991;Perry et al 2011;Heuer et al 2012;Salter et al 2012Salter et al , 2017Salter et al , 2018.…”
mentioning
confidence: 99%
“…Genome completeness was measured by calculating the number of Actinopterygii single copy orthologs retained in the assembly via BUSCO (91) with the actinopterygii_odb10 database. Completeness was further assessed with read mapping rate by mapping publicly available paired-end Illumina short read RNA (47) and DNA (PRJNA196921) libraries, as well as input HiFi reads to the super-scaffolded assembly.…”
Section: Nuclear Genome Assemblymentioning
confidence: 99%
“…Transfer RNAs (tRNAs) were predicted using trnascan v1.4.0 (111). Gene models were then refined and UTRs added with funannotate::update (46) using IsoSeq high quality transcripts and O.beta illumina short reads (PRJNA313355; (47).…”
Section: Gene Modelsmentioning
confidence: 99%